The Exploitation of Appropriateness Conditions in A Comedy (She Stoops to Conquer) - Siti Hanifa (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2008)
The Exploitation of Appropriateness Conditions in A Comedy (She Stoops to Conquer)